Optimalisasi Fermentasi Bioetanol dari Kulit Durian Lokal (Durio zibethinus) dengan Penambahan Vitamin B Kompleks Sebagai Bahan Bakar Rumah Tangga - Rafi Rijal Mufaiq; M. Nuril Yazdan Al-Firdhaus; Giesty Trienita; Widayoko, Agus (Jurnal Integrasi Sains dan Quran, 2026)
Indonesia still faces a high dependence on LPG, making the development of more sustainable alternative energy sources necessary. On the other hand, durian peel waste is abundant but has not been optimally utilized as a raw material for bioethanol. The low efficiency of lignocellulosic biomass fermentation remains a major obstacle; therefore, the aim of this study is to determine the effectiveness of adding B-complex vitamins to bioethanol production by examining the resulting ethanol content. The type of research conducted is descriptive research with a quantitative data approach. Data were collected through literature studies, observations, and experiments. The research procedures included delignification, hydrolysis, fermentation for 6 and 7 days, and distillation. To determine product effectiveness, analyses of ethanol content, density, and flash point were carried out. The results show that the addition of B-complex vitamins significantly increases the quality of bioethanol, with ethanol levels reaching 99.5% on day 6 and 97.7% on day 7, higher than without vitamin addition. The density ranged from 0.7992 to 0.8315 g/ml, which is close to the SNI 7390:2012 standard, while the flash point of 11–12°C indicates good ethanol purity. Thus, durian peel waste has potential as a second-generation bioethanol feedstock, and B-complex vitamins have been proven to improve fermentation efficiency and the quality of the resulting ethanol based on ethanol content analysis.